To what extend the heritage sites/attractions in U.K. have adopted digital marketing to meet the emerging consumer needs and behavior - Liu, Xiaomin (2016)
Digital marketing seems to be one of the most popular marketing concept in recent years. The raising of digital media has considerably changed people’s life and how they interact with the brand. Facing the raising power from the customer side, companies/organizations in a wild range have transformed to this new marketing paradigm, leveraging multiple digital media and inventions to interact with their consumer and invite them to create the experience together. As a service business, Tourism industry has also experienced this change significantly. And as a big part of the business, heritage sites and attractions are also hugely linked with this new marketing concept. As Michael Porter said: “The key question is not whether to deploy Internet technology – companies have no choice if they want to stay competitive – but how to deploy it.” In this case, this paper aims to interrogate how the heritage sites have adopted digital marketing to match the new customer behavior and needs. Based on the review of the academic achievement in three related areas – Digital Marketing, Tourism Marketing and Heritage Marketing, a conceptual framework will be built for assessing several representative heritage sites in U.K. according to the wide accepted academic standard. From the analysis, the paper is trying to give a general and basic picture about the status of theoretical study on digital marketing towards heritage sites and how digital marketing has been used in the practical side.